Christmas - Macdonald, Fiona (Luton : Andrews UK, 2012)
Just when you thought it was safe to take a sneak peek into your stocking, it's 'Christmas: A Very Peculiar History'. Taking an unbiased view of the myth and mystery surrounding the origins of the yuletide season, this book introduces mindbending facts about the holiday season and shatters the myths surrounding some of Christmas' most treasured and well-known facets: When exactly was Jesus born? Why is Santa's outfit red and white? Where do we get Christmas trees from? What's the snow in a s ...
Cover; Contents; Front Matter; Title Page; Publisher Information; Quotes; Putting Christmas on the Map; Christmas; Introduction; Chapter One; Chapter Two; Chapter Three; Chapter Four; Chapter Five; Chapter Six; Chapter Seven; Chapter Eight; Chapter Nine; Glossary.
Description based on print version record.
Keywords: Christmas -- History; Social Science; RELIGION / Holidays / Christmas & Advent; Electronic books